Research Involving Health Providers and Managers: Ethical Issues Faced by Researchers Conducting Diverse Health Policy and Systems Research in Kenya. Issue 3 (4th October 2016) - Molyneux, Sassy; Tsofa, Benjamin; Barasa, Edwine; Nyikuri, Mary Muyoka; Waweru, Evelyn Wanjiku; Goodman, Catherine; Gilson, Lucy
Abstract: There is a growing interest in the ethics of Health Policy and Systems Research (HPSR), and especially in areas that have particular ethical salience across HPSR. Hyder et al (2014) provide an initial framework to consider this, and call for more conceptual and empirical work. In this paper, we respond by examining the ethical issues that arose for researchers over the course of conducting three HPSR studies in Kenya in which health managers and providers were key participants. All three studies involved qualitative work including observations and individual and group interviews. Many of the ethical dilemmas researchers faced only emerged over the course of the fieldwork, or on completion, and were related to interactions and relationships between individuals operating at different levels or positions in health/research systems. The dilemmas reveal significant ethical challenges for these forms of HPSR, and show that potential 'solutions' to dilemmas often lead to new issues and complications. Our experiences support the value of research ethics frameworks, and suggest that these can be enriched by incorporating careful consideration of context embedded social relations into research planning and conduct. Many of these essential relational elements of ethical practice, and of producing quality data, are given stronger emphasis in social science research ethics than in epidemiological, clinical or biomedical research ethics, and are particularly relevant where health systems are understood as social and political constructs. We conclude with practical and research implications.